78.3k views
3 votes
-3x^4+27x^2+1200=0

Please show all steps

User Ciel
by
6.3k points

1 Answer

2 votes

Answer:

x = 5, -5, 4i, -4i ;
\mathbf{√(-1)=i}

Explanation:


3\textrm{x}^(4)-27\textrm{x}^(2)-1200=0

assume
\textrm{x}^(2)=\textrm{t}


3\textrm{t}^(2)-27\textrm{t}-1200=0

Now the above equation is a quadratic equation.

There are two solutions of any quadratic equation. Solution of a quadratic equation
\mathbf{a\textrm{x}^(2)+b\textrm{x}+c=0} is given by:


\mathbf{\textrm{x}=\frac{-b+\sqrt{b^(2)-4ac}}{2a},\textrm{x}=\frac{-b-\sqrt{b^(2)-4ac}}{2a}}

similarly there are two solutions of the quadratic equation
3\textrm{t}^(2)-27\textrm{t}-1200=0 which are:


\textrm{t}=\frac{-b+\sqrt{b^(2)-4ac}}{2a}=\frac{-(-27)+\sqrt{(-27)^(2)-4 \cdot 3 \cdot (-1200)}}{2 \cdot 3}=25,\\ \textrm{t}=\frac{-b-\sqrt{b^(2)-4ac}}{2a}=\frac{-(-27)-\sqrt{(-27)^(2)-4 \cdot 3 \cdot (-1200)}}{2 \cdot 3}=-16

Since
\textrm{x}^(2)=\textrm{t}

Therefore
\textrm{x}^(2)=25,\textrm{x}^(2)=-16


\textrm{x}^(2)=25 \Rightarrow \textrm{x}=+√(25),-√(25) \Rightarrow \textrm{x}=5,-5


\textrm{x}^(2)=-16 \Rightarrow \textrm{x}=+√(-16),-√(-16) \Rightarrow \textrm{x}=√(-1) \cdot √(16),-√(-1) \cdot √(16) \Rightarrow \textrm{x}=4i,-4i ; where
\textrm{i}=√(-1) (the numbers with 'i' are called imaginary numbers)

Therefore
\mathbf{x=5,-5,4i,-4i}

User ExpExc
by
6.0k points